2013
DOI: 10.1016/j.bjane.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Rate as a Predictor of Weaning Failure from Mechanical Ventilation

Abstract: RR was an effective predictor of weaning failure. The best cut-off point was RR > 24 rpm, which differed from those reported in the literature (35 and 38 rpm). Only 6% of patients were reintubated, but RR or other weaning criteria did not identify them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…After completion of SBT, patients in Group F had significantly higher respiratory rates than those in Group S. The findings are similar to research by Lima et al . [ 25 ], who suggested that a respiratory rate with a cut-off value of 24 breaths per minute was a predictor of weaning failure.…”
Section: Discussionmentioning
confidence: 99%
“…After completion of SBT, patients in Group F had significantly higher respiratory rates than those in Group S. The findings are similar to research by Lima et al . [ 25 ], who suggested that a respiratory rate with a cut-off value of 24 breaths per minute was a predictor of weaning failure.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory rate has been reported as an effective of weaning failure; the best cut-off point > 24 breaths per minute had a sensitivity of 100%, specificity of 85%, and accuracy of 88%. 19 Furthermore, respiratory rate is incorporated into the more commonly used index to predict weaning failure, the rapid shallow breathing index (RSBI). A rapid shallow breathing index higher than 105 during the SBT is considered highly predictive of weaning failure.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ventilators also often causes several effects in the form of respiratory tract infections, inflammation of the throat wall, or mucosa [18]. In a severe condition, it may cause respiratory failure due to narrowing of the respiratory tract due to swelling of the airways due to respiratory tract infections [19], [20]. This is because the air that enters the respiratory tract or lungs is still classified as dry air, which can trigger inflammation of the mucous layer or the outermost membrane of the throat [21].…”
Section: Introductionmentioning
confidence: 99%